MENULIS TEKS PROSEDUR MENGGUNAKAN MODEL PEMBELAJARAN NEUROLINGUISTIC PROGRAMMING (NLP) DI SMK - Wikanengsih - Wikanengsih (Jurnal Semantik, 2021)
This study aims to describe the implementation of learning, teacher and student responses, and to find out the difficulties experienced by class X SMK students in completing tasks in learning to write procedural texts using the NLP model. The research method used was descriptive quantitative with a sample of 38 students of SMK class X TO. The results obtained are as follows: (1) the implementation of learning is carried out in two meetings with the results of observations showing a very good category (2) the teacher's response to the implementation of learning is at a very good level, as well as student responses. (3) students' difficulties in implementing learning, namely when answering questions related to aspects of knowledge and skills in diction or word choice.